Asthma and other allergic conditions in Colombia: A study in 6 cities (2004)
Background No detailed information is available on the burden and impact of allergic diseases simultaneously for adults and children in Colombia and most Latin American countries. Objectives To investigate the prevalence of asthma, allergic rhinitis, and atopic dermatitis symptoms in 6 cities in Colombia; to measure patient expenses and school days and workdays lost; to describe disease severity; and to determine levels of total and specific IgE in asthmatic subjects. Methods A multistage stratified random sample selection of schools with subjects aged 5 to 18 years in each city was used. Guardian subjects selected were contacted, and home visits were arranged. Subjects aged 1 to 4 years and older than 19 years were also selected randomly by systematic sampling based on the addresses of the subjects aged 5 to 18 years. Subjects with asthma symptoms were invited to provide a blood sample. Results Information was obtained from 6,507 subjects. The prevalence of asthma, rhinitis, and atopic dermatitis symptoms in the past 12 months was 10.4% (95% confidence interval [CI], 9.7%–11.1%), 22.6% (95% CI, 21.6%–23.6%), and 3.9% (95% CI, 3.4%–4.4%), respectively. Thirty-eight percent of asthmatic subjects had visited the emergency department or have been hospitalized, and 50% reported lost school days and workdays. Seventy-six percent of sampled asthmatic patients were considered to be atopic. Conclusions The burden of disease and societal consequences of allergic entities in urban settings in countries such as Colombia are of concern but are largely ignored, perhaps because of the misconception that these diseases are of public health importance only in industrialized nations.